Impact of Opioid-Free Anesthesia on Postoperative Quality of Recovery in Patients After Laparoscopic Cholecystectomy: A Randomized Controlled Trial [Letter] - Xue B (Dove Medical Press, 2024)
Bai Xue Department of Anesthesiology, Sengkang General Hospital, SingaporeCorrespondence: Bai Xue, Department of Anesthesiology, Sengkang General Hospital, 110 Sengkang E Way, 44886, Singapore, Tel +65-97748254, Email bxue0919@gmail.com